Assessments of Perfusion, Blood Flow, and Vascular Structure in Ambulatory Subjects: Guidance for Translational Research Scientists - Schonberger, Zachariah G.; Huang, Sophie J.Y.; Thakkar, Radhika N.; Mamone, Amar A.; Khan, Daniyal I.; Chow, Natalie L.Y.; Ahmed, Moeiz; Sivaram, Namashi; Bao, Yuki; Kesavan, Vihirthan; Côté, Jordan; Sun, Clara; et al. (Journal of vascular research, 2023)
Research involving human subjects in ambulatory settings is a critical link in the chain comprising translational research, spanning preclinical research to human subject and patient cohort studies. There are presently a wide array of techniques and approaches available to investigators wishing to study blood flow, perfusion, and vascular structure and function in human subjects. In this multi-sectioned review, we discuss capillaroscopy, carotid intima-media thickness, flow-mediated dilation, laser Doppler flowmetry, near-infrared spectroscopy, peripheral arterial tonometry, pulse wave velocity, retinal fundus imaging, and vascular plethysmography. Each section contains a general overview and the physical basis of the technique followed by a discussion of the procedures involved and the necessary equipment, with attention paid to specific requirements or limitations. Subsequently, we detail which aspects of vascular function can be studied with a given technique, the analytical approach to the collected data, and the appropriate application and limitation(s) to the interpretation of the data collected. Finally, a modified scoping review provides a summary of how each assessment technique has been applied in previous studies. It is anticipated that this review will provide an efficient source of information and insight for preclinical investigators seeking to add translational aspects to their research programs.